Kepemimpinan Inklusif sebagai Penggerak Perilaku Kerja Inovatif - Adi Purwanto; Adijati Utaminingsih; Ahmad Kholid; Abdul Aziz (Journal of Economics and Management Scienties, 2026)
Innovative work behavior is a key factor in enhancing organizational competitiveness, particularly in the garment industry, where companies are required to adapt to rapidly changing market conditions and continuously improve operational efficiency. This study aims to examine the effect of Inclusive Leadership on Innovative Work Behavior, with Psychological Safety serving as a mediating variable. A quantitative explanatory research design was employed. Data were collected through questionnaires administered to 175 permanent employees of garment companies in Semarang Regency, selected using a purposive sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that Inclusive Leadership positively enhances Innovative Work Behavior while also strengthening employees' Psychological Safety. Furthermore, Psychological Safety contributes to the improvement of innovative work behavior and partially mediates the relationship between Inclusive Leadership and Innovative Work Behavior. These findings indicate that leadership characterized by openness, respect for diversity, and active employee involvement fosters a psychologically safe work environment. Such an environment encourages employees to express ideas confidently, explore new approaches, and actively contribute to workplace innovation. This study extends the existing literature on inclusive leadership and innovative work behavior while providing practical insights for organizations seeking to cultivate an innovation-oriented culture through inclusive leadership practices and the development of a psychologically safe work environment.